Contrasting CO2 Dynamics in Seagrass Meadows Between Organic Carbon (OC)‐Rich Reef and OC‐Poor Terrestrial Sediments: Implications for Enhanced Alkalinity Production - Wen‐Chen Chou; Lan‐Feng Fan; Mariche B. Natividad; Jian‐Jhih Chen; Zih‐Wei Tang; Huei‐Fen Chen; Ping‐Chun Chen; En‐Cheng Kong; Yung‐Yen Shih; Wei‐Jen Huang; Chin‐Chang Hung (Geophysical Research Letters)
Abstract Seagrass meadows are increasingly recognized across the globe as a natural climate solution due to their significant potential in alkalinity‐driven carbon dioxide (CO2) removal, which possibly represents an overlooked component of ocean carbon removal. This study comprehensively investigated the carbonate chemistry, sediment carbon content, mineral composition, and benthic alkalinity fluxes in two distinct sites with tropical seagrass meadows: one situated in organic carbon (OC)‐rich reef sediments and the other in OC‐poor terrestrial sediments. Results showed nearly two orders of magnitude higher benthic alkalinity fluxes in the OC‐rich reefs than in OC‐poor sediments (72.8 ± 64.4 vs. 0.53 ± 0.99 mmol m−2 d−1). This can further substantially increase alkalinity levels and reduce the partial pressure of CO2 in the overlying seawater, thereby enhancing the capacity for CO2 uptake. We propose that seagrass meadows on high‐OC reef sediments, the hotspots for alkalinity generation, could amplify the climate change mitigation potential of seagrass restoration initiatives.